Financial development, institutional quality, and financial risk of conventional and Islamic banks - Saidi, Normaizatul Akma (2018)
Both conventional and Islamic banks are vital for the economy as financial intermediary, which serve to channel excess funds to those who face fund shortage. This empirical study was propelled by the inconclusive evidences on the effects of financial development and institutional quality towards financial risk (liquidity risk and credit risk) for conventional and Islamic banks. In the context of conventional and Islamic banks, this study aimed to (1) evaluate the moderating effects of institutional quality on the relationship between financial development and financial risk for conventional and Islamic banks; (2) evaluate the effects of institutional quality (government effectiveness and regulatory quality) towards their financial risk; and (3) identify the determinants of their liquidity risk and credit risk (financial risk). This study adopted multivariate panel regression analysis, specifically, static panel regression analysis as an estimation method. Data between 2006 and 2014 were obtained from 392 banks (297 conventional banks and 95 Islamic banks) in 17 countries within three primary regional Islamic banking hubs (Middle East, Southeast Asia, and South Asia). With respect to the first objective, the relationship between financial development and liquidity risk was only moderated by regulatory quality for conventional banks. However, both measures of institutional quality moderated the relationship of financial development and financial risk for Islamic banks. Meanwhile, empirical findings revealed that the financial development affected only liquidity risk for conventional banks whereas as for Islamic banks, both financial risk was not affected. In line with the second objective, institutional quality was found to affect liquidity risk and only government effectiveness affect credit risk for conventional banks, but as for Islamic banks, institutional quality not affected their financial risk. With respect to the third objective, both measures of financial risk were affected by different factors—bank size and capitalization affected financial risk for conventional banks while bank size and capitalization affected only liquidity risk for Islamic banks. Additionally, technical efficiency affected only liquidity risk while global financial crisis affected only credit risk for conventional banks. As for Islamic banks, global financial crisis affected financial risk. Hence, appropriate mechanism to improve the risk management of banks can be determined by regulators or policymakers. Subsequently, identifying specific dimensions of institutional quality serves as guidance for designing related policies and regulations. Conclusively, it is highly recommended for investors to focus on the potential risk imposed by conventional and Islamic banks for low-risk investment.